Plan de marketing para el posicionamiento del Centro de Acopio Corrales Tapia en el cantón Guaranda, provincia Bolívar, período 2023 – 2027 - Villamar Muñoz, Marlene Michel (2024)
This project is based on the implementation of a marketing plan for the positioning of the Corrales Tapia Collection Center in Guaranda Canton, Bolivar Province. To know if the research hypothesis is feasible or not, the qualitative approach will be used for the research study, starting from this point by analyzing the current situation of the Collection Center.